We are not walking wave functions. A response to "Quantum Mind and Social Science" by Alexander Wendt. (30th March 2018) - Donald, Matthew J.
Abstract: Alexander Wendt raises many interesting questions in this book, but to get to the answers he wants, he relies on a misunderstanding of the nature of the quantum states of macroscopic objects.